Pengaruh Pengungkapan Environmental, Social, and Governance (ESG) terhadap Keputusan Investasi: Regulasi Pemerintah sebagai Variabel Moderasi - Azzakhusna, Famita; Triyono, Triyono; Hidayati, Arina (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The purpose of this study is to examine the influence of Environmental, Social, and Governance (ESG) disclosure on investment decisions, with government regulations as a moderation variable. The motivation for this research is the growing investor interest in corporate sustainability practices and the importance of regulation in enhancing the credibility of ESG information in the capital market. This study uses an explanatory quantitative approach. The data used is secondary data obtained from the company's annual reports, sustainability reports, and ESG databases listed on the Indonesia Stock Exchange for the period 2020-2024. The research sample was selected using a purposive sampling technique. SPSS 27 was used for data analysis, with Panel data regression and Moderated Regression Analysis (MRA) applied. The results show that ESG disclosures have a positive and significant impact on investment decisions. These findings imply that companies with higher levels of ESG disclosure are associated with fewer negative investment responses from investors. In addition, government regulations have been found to strengthen the link between ESG disclosures and investment decisions across environmental, social, and governance dimensions. The results are consistent with the theory of Perceived Firm Legitimacy, which holds that a company's legitimacy increases when it meets the social and regulatory expectations that apply to it. This research theoretically contributes to the development of ESG literature and corporate legitimacy, as well as has practical implications for companies and regulators, by improving the quality of ESG disclosure and the effectiveness of sustainability regulations to support sustainable investments.